Pemaknaan Penonton Remaja di Jakarta terhadap Operasi Plastik dalam Drama Korea My ID is Gangnam Beauty - Nurul Fauziah; Ratna Puspita (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2022)
This study aims to explore the audience receptions, focusing on adolescents aged 10-24 years in Jakarta, about plastic surgery in the Korean drama "My ID is Gangnam Beauty". This drama tells about plastic surgery in South Korea, while the audience in Jakarta already has an understanding of plastic surgery which has been constructed by society. This study uses Stuart Hall's reception analysis which does not focus on the meaning in Korean dramas, but rather the meaning created in the interaction between the audience and the Korean drama. The audience can have a variety of meanings for plastic surgery in Korean dramas that show a dominant position, negotiation, and opposition. The results showed that adolescent reception towards plastic surgery in the Korean drama "My ID is Gangnam Beauty" is negotiation. The audiences stated that women free to change their appearance through plastic surgery so they can make friends and not experience bullying, but criticized the part of the story that depicts a female character who needs a man to build her self-confidence. The audience realizes that Korean drama fills its story about plastic surgery and certain beauty standards. However, the audience also uses the message in this drama to criticize how society dictates the acceptance of the body, as is the case in Indonesia.